Analysis of E-Commerce Supervision for the Protection of Spiritual Rights of Consumers - Rachma Ayu Handari; Triyono Adi Saputro (www.amertainstitute.com, 2025)
This research aims to juridically analyze e-commerce supervision in the context of protecting consumers' spiritual rights based on Law Number 11/2008 on Electronic Information and Transactions (ITE Law), specifically Article 28, paragraph (1). The method used is normative legal research with a statutory and conceptual approach, which examines written legal norms and the principle of legality to test the certainty and clarity of these norms in the context of electronic transactions. Data is collected through a literature study, including primary and secondary legal materials such as laws, court decisions, and accredited journal articles. The analysis was conducted qualitatively by interpreting legal norms and evaluating the basic principles of applicable law. This research concludes that Article 28 paragraph (1) of the ITE Law expressly regulates the prohibition of spreading news that is detrimental to consumers and is an entry point to provide preventive and repressive protection of the spiritual rights of E-Commerce consumers. However, the obstacles are the multiple interpretations of proving the elements of digital offences and the coordination of law enforcement across sectors that hamper the effectiveness of supervision. This research contributes to designing regulations for the legal protection of consumers' spiritual rights in the digital era and by determining the implementation of comprehensive e-commerce supervision